TINDAK PIDANA PERDAGANGAN ORANG (HUMAN TRAFFICKING) SEBAGAI TRANSNATIONAL CRIME - Kadek Novi Darmayanti; Komang Febrinayanti Dantes; Si Ngurah Ardhya; Muhamad Jodi Setianto (Ganesha Law Review, 2022)
Human trafficking is one of the transnational crimes that is a threat to global security which is one type of transnational crime coupled with illicit drug trafficking, maritime piracy, arms smuggling, money laundering, terrorism, international banking crimes and cybercrimes. The forms of trafficking in persons are divided based on the purpose of delivery, based on the victim, and based on the form of exploitation. Because of the massiveness of this crime, the United Nations formulated a protocol called the Palermo Protocol. In Indonesia, there are also special regulations regarding the criminal act of trafficking in persons, namely Law Number 21 of 2007. Although there are already laws and regulations that regulate this crime, in fact it is still not able to provide a sense of justice as well as security and comfort for victims of the crime of trafficking in persons. Other legal protections are still needed for victims of this crime.